Uncontrolled asthma across GINA treatment steps 2 − 5 in a large US patient cohort. (4th May 2022) - Busse, William W.; Fang, Juanzhi; Marvel, Jessica; Tian, Hengfeng; Altman, Pablo; Cao, Hui
Abstract: Objective: Despite advances in treatment, asthma remains uncontrolled in many patients, with increased risk of exacerbation and associated healthcare resource utilization (HCRU). We describe patient characteristics, exacerbations, asthma control, and HCRU using GINA treatment step (GS) as a proxy for asthma severity.  Methods: Using a large, US, health-claims database, 4 longitudinal cohorts of 517, 738 patients in GS2–5, including a subgroup of patients with baseline eosinophil (EOS) counts, were analyzed retrospectively (study period 2010 − 2016). Index for each cohort was patients' first time entering the GS, determined by first claim of first regimen. Uncontrolled asthma was defined according to published criteria as a multi-dimensional measure that includes number of exacerbations. Key variables including, baseline characteristics, post-index exacerbations, and HCRU (all-cause and asthma-specific events) are summarized by descriptive statistics. Results: Uncontrolled asthma was reported in 19.8% patients in GS2, 44.8% in GS3, 49.3% in GS4, and 58.6% in GS5. Annualized mean (SD) rates of exacerbation 12 months post-index generally increased across GS2–5 (0.26 [0.86], 0.32 [0.79], 0.36 [0.83], 0.29 [0.86], respectively). HCRU also increased with increasing GS, with higher HCRU among the uncontrolled cohort within each GS. In patients with EOS ≥300 cells/µL, uncontrolled asthma also increased with increasing GS (21.8%, 43.9%, 50.5%, 67.2% for GS2–5, respectively). Conclusions: This large database study provides real-world evidence of the substantial degree of uncontrolled asthma in US clinical practice across GS, supporting calls for better asthma management. Healthcare burden tends to increase with lack of control in all groups, highlighting the need for improved patient education, adherence, access, and treatment optimization. Supplemental data for this article can be accessed at publisher's website.